2015
DOI: 10.1007/s10562-015-1563-y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ and Simultaneous Synthesis of a Novel Graphene-Based Catalyst for Deep Hydrodesulfurization of Naphtha

Abstract: In this research, a novel graphene-supported catalyst was prepared through which, a simultaneous chemical exfoliation of graphite and MoS 2 powder performed preparing a new composite species and evaluated for the hydrodesulfurization reaction of naphtha and no sulfidation pretreatment was performed upon the catalyst. Also, the influences of the operating parameters such as temperature, and liquid hourly space velocity on HDS conversion evaluated.Electronic supplementary material The online version of this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Shan et al (2015) have utilized NiW catalysts for selective HDS of FCC naphtha, and it was reported that better dispersion of W enables modification of the active phase which results in higher selective HDS. Also, various graphene-supported catalysts have been used for HDS of naphtha (Hajjar et al 2015(Hajjar et al , 2016(Hajjar et al , 2017a. MoS 2 supported over graphene was used for HDS of naphtha for which a simultaneous chemical exfoliation method was followed for preparing the catalyst by which high conversion was obtained (Hajjar et al 2015).…”
Section: Edited By Xiu-qin Zhumentioning
confidence: 99%
See 1 more Smart Citation
“…Shan et al (2015) have utilized NiW catalysts for selective HDS of FCC naphtha, and it was reported that better dispersion of W enables modification of the active phase which results in higher selective HDS. Also, various graphene-supported catalysts have been used for HDS of naphtha (Hajjar et al 2015(Hajjar et al , 2016(Hajjar et al , 2017a. MoS 2 supported over graphene was used for HDS of naphtha for which a simultaneous chemical exfoliation method was followed for preparing the catalyst by which high conversion was obtained (Hajjar et al 2015).…”
Section: Edited By Xiu-qin Zhumentioning
confidence: 99%
“…Also, various graphene-supported catalysts have been used for HDS of naphtha (Hajjar et al 2015(Hajjar et al , 2016(Hajjar et al , 2017a. MoS 2 supported over graphene was used for HDS of naphtha for which a simultaneous chemical exfoliation method was followed for preparing the catalyst by which high conversion was obtained (Hajjar et al 2015). Co-Mo supported over graphene oxide has been used for performing the naphtha HDS reaction in which metallic phases were impregnated onto the support via the hydrothermal and wetness impregnation method (Hajjar et al 2017a, b).…”
Section: Edited By Xiu-qin Zhumentioning
confidence: 99%
“…Therefore, the amount of sulfur and nitrogen compounds in fuels should be decreased to provide a clean environment. Hydrodesulfurization (HDS) (Gao et al, 2011;González-Cortés et al, 2006;Hajjar et al, 2015Hajjar et al, , 2016aHajjar et al, , 2017aHajjar et al, , 2017bHuirache-Acuña et al, 2012;Mendoza-Nieto et al, 2015;Miller et al, 2000;Shan et al, 2015) and hydrodenitrogenation (HDN) (Sundaramurthy et al, 2006;Zepeda et al, 2016) are the main processes considered for reducing the Total Sulfur (T.S.) and Total Nitrogen (T.N.)…”
Section: Introductionmentioning
confidence: 99%
“…Many various carbon structures with an expanded pore system, including graphene-based materials [13] and nanofibers [14], were developed. Among them, ordered mesoporous carbons (OMCs) seem to be ideal candidates to overcome foregoing drawbacks of ACs.…”
Section: Introductionmentioning
confidence: 99%